2020
DOI: 10.1155/2020/8846273
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Analysis of Furcation Areas of Multirooted Teeth in a Tunisian Population

Abstract: Aims. The aim of the study was to evaluate the morphological characteristics of furcation of permanent molars in Tunisian population. Materials and Methods. One hundred and four extracted maxillary and mandibular permanent molars were included in this study; comprising 34 maxillary first molars, 18 maxillary second molars, 33 mandibular first molars, and 19 mandibular second molars. For each tooth, the vertical dimension of the root trunk, root length, and interradicular space width were assessed with a microm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…First molars of non-periodontitis patients had significantly greater distances to furcation than periodontitis patients. This is in agreement with a previous study [ 21 ] that reported that the root trunk of the first molar was greater than the second and third molars with an average distance of 2.6 mm, making it less prone to periodontal diseases.…”
Section: Discussionsupporting
confidence: 93%
“…First molars of non-periodontitis patients had significantly greater distances to furcation than periodontitis patients. This is in agreement with a previous study [ 21 ] that reported that the root trunk of the first molar was greater than the second and third molars with an average distance of 2.6 mm, making it less prone to periodontal diseases.…”
Section: Discussionsupporting
confidence: 93%
“…The furcation area presents unique situations and challenges that limit the application of routine periodontal therapy. The special anatomy and morphology of the furcation area necessitate an array of special procedures and modified treatment approaches to overcome various confounding factors such as the size and shape of the furcation roof, entrance and the divergence of the roots along with the alveolar housing, and the varied nature and patterns of periodontal destruction [ 16 ]. Furcation plasty (osteoplasty, odontoplasty and root planing) is performed at the furcation level.…”
Section: Reviewmentioning
confidence: 99%
“…1 The topography of such multirooted tooth prevents appropriate instrumentation access which in turn allows pathogenic microbial flora to persist and renders them inaccessible for periodontal therapy. 2 Effective management of the furcation area necessitates a better understanding of the furcation and root surface anatomy. 2 There is paucity of literature accessing the root surface concavities and morphometric measurements of the furcation area of the maxillary first premolar teeth in Nepalese population.…”
Section: Introductionmentioning
confidence: 99%
“…2 Effective management of the furcation area necessitates a better understanding of the furcation and root surface anatomy. 2 There is paucity of literature accessing the root surface concavities and morphometric measurements of the furcation area of the maxillary first premolar teeth in Nepalese population. This study aimed to assess the presence of concavities on the root surface as well as morphometric measurement of the root trunk beyond the CEJ were excluded.…”
Section: Introductionmentioning
confidence: 99%